(untitled) (Heritage, 2025)
Slobodan Jovanović was one of the most prominent Serbian and Yugoslav scholars of the late 19th and mid-20th centuries. His works span a wide range of academic disciplines, placing him among the most distinguished jurists, historians, writers, literary critics, and political scientists in the former Yugoslavia. In terms of his career, he served as a university professor, Dean of the Faculty of Law in Belgrade, Rector of the University of Belgrade, and President of the Serbian Royal Academy. In the realm of public engagement, he participated as an expert at the Paris Peace Conference in 1919. He was also the President of the Serbian Cultural Club from 1937 to 1941. Following the military coup of March 27, 1941, in the later years of his life, Jovanović became actively engaged in practical politics for the first time. It was during this period that he began applying his political theory in real-world governance. In the coup-installed government led by General Dušan Simović, Jovanović served as Deputy Prime Minister from March 27, 1941, to January 11, 1942. He subsequently assumed the role of Prime Minister of the Royal Yugoslav Government-in-Exile in London, holding this position from January 11, 1942, until June 26, 1943. After the Second World War, Jovanović authored memoirs that provide valuable insight into the evolution of his political thought during exile, offering a contrast with the theoretical frameworks he developed prior to the war. His reflections reveal critical dimensions of the diplomatic and political relations between the Yugoslav government-in-exile and the United Kingdom. Notably, Jovanović expressed dissatisfaction with several aspects of British foreign policy, particularly its approach toward Yugoslavia and the Serbian people. A staunch supporter of General Dragoljub Mihailović’s movement—which he viewed as both lawful and legitimate—Jovanović worked to secure international recognition of Mihailović’s forces as the official Yugoslav Army in the Homeland. These efforts, however, failed to yield results, as neither Britain nor the other Allied powers extended formal support or recognition. This ultimately culminated in disappointment and condemnation in his homeland. Jovanović’s writings also shed light on deep internal divisions within the government-in-exile, particularly the tensions with Croatian representatives. These unresolved frictions, combined with shifting geopolitical realities, culminated in the signing of the Šubašić–Tito Agreement and Jovanović’s subsequent withdrawal from political life. Slobodan Jovanović spent the end of the war in exile, where he remained until his death on December 12, 1958. As a member and later Prime Minister of the Yugoslav government-in-exile—which sought to preserve the continuity of the pre-war regime—he was tried and convicted in absentia by the new Yugoslav authorities. For a quarter of a century, his works were consigned to oblivion, remaining largely inaccessible until 1990. He was officially rehabilitated in 2007.